Contagious charisma: the flow of charisma from leader to followers and the role of followers’ self-monitoring - Katz-Navon, Tal; Delegach, Marianna; Haim, Eden (Frontiers in Psychology, 2023)
Leadership flows down from leader to followers. It is unclear, however, whether and when a leader’s charisma may also be transferred to followers, since charisma is a more leader-centric leadership style. Integrating insights from the social learning, emotional contagion, and self-concept theories, we argue that charisma can cascade downward from the leader to followers and that this effect is contingent on the individual follower’s level of self-monitoring. Measuring a sample of 127 followers and 15 leaders in a large organization at two time points, we found that throughout time, the leader’s charisma indeed cascaded down to followers. However, this effect was prominent only for low-monitoring followers. Novel insights into the flow-down effect of charisma, avenues for future research, and practical implications are discussed.